2022
DOI: 10.1002/ptr.7615
|View full text |Cite
|
Sign up to set email alerts
|

Lutein ameliorates high‐fat diet‐induced obesity, fatty liver, and glucose intolerance in C57BL/6J mice

Abstract: Obesity is a multi‐factorial metabolic syndrome that increases the risk of cardiovascular diseases, diabetes, and cancer. We recently demonstrated the antiadipogenic efficacy of lutein using a 3 T3‐L1 cell culture model. This study aimed to examine the antiobesity efficacy of lutein on high‐fat (60% kcal fat) diet‐induced C57BL/6J obese mice model. Lutein (300 and 500 μM), Orlistat (30 mg/kg body weight ‐ positive control), and its combination (orlistat, 15 mg/kg body weight+lutein, 300 μM) were administered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…We previously found that GDM increased the incidence of large-for-gestational-age (LGA) births in this cohort [ 16 ]. There was evidence in animals that lutein supplementation alleviated obesity in rodents fed a high-fat diet [ 31 ]. We thus examined the association between maternal L + Z intake or status and neonatal length and weight, but did not identify any significant associations ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found that GDM increased the incidence of large-for-gestational-age (LGA) births in this cohort [ 16 ]. There was evidence in animals that lutein supplementation alleviated obesity in rodents fed a high-fat diet [ 31 ]. We thus examined the association between maternal L + Z intake or status and neonatal length and weight, but did not identify any significant associations ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…While lutein levels may be impacted by lipid metabolism, recent research suggests that lutein intake may also affect lipid metabolism by serving as an antioxidant to prevent peroxidation of lipoproteins and increasing peroxisome proliferators activated receptors (PPAR)-α gene expression, which promotes fatty acid catabolism, thereby reducing adiposity and improving cardiometabolic health [ 53 , 54 ]. Lutein supplementation was found to reduce the risk of obesity and glucose intolerance in high-fat-diet-fed rodents [ 31 ]. A major adverse outcome of GDM is fetal overgrowth or macrosomia at birth due partly to the excess fat accretion of the fetus [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lutein is a powerful antioxidant that can neutralize free radicals and reactive oxygen species, which can cause oxidative damage to cells and tissues. It can help protect cells from oxidative stress and reduce the risk of chronic diseases such as cancer, cardiovascular disease, and neurodegenerative disorders [ 185 ]. Chronic inflammation is associated with numerous health problems, including arthritis, asthma, and heart disease.…”
Section: Resultsmentioning
confidence: 99%
“…The escalation of energy intake can precipitate a derangement in energy metabolism, ultimately fostering lipid accumulation within both adipose tissue and the liver, culminating in obesity [ 23 ]. Mice subjected to HFD, mirroring obesity and its concomitant disorders such as NAFLD, have become a frequently adopted animal model [ 24 ].…”
Section: Discussionmentioning
confidence: 99%